An anti-infective hydrogel adhesive with non-swelling and robust mechanical properties for sutureless wound closure. Issue 26 (5th June 2020) - Du, Xinchen; Hou, Yujie; Wu, Le; Li, Shilin; Yu, Ao; Kong, Deling; Wang, Lianyong; Niu, Guiling
Abstract : An anti-infective TA/hydrogel with non-swelling and adhesion properties could close wounds in a non-invasive way. Abstract : A non-swelling hydrogel adhesive is urgently needed in clinical application for wound closure; however, preparing a non-swelling hydrogel adhesive with superior mechanical and tissue adhesion properties remains a challenge. In this study, we developed a new family of non-swelling hydrogel adhesives composed of Pluronic F127 diacrylate, poly(ethylene glycol) diacrylate, modified sodium alginate, and tannic acid. Physical and biological properties of the hydrogels were systematically evaluated in vitro/vivo . The results indicated that the hydrogels exhibited non-swelling features, robust mechanical properties and good adhesion abilities toward various tissues. The hydrogels also exhibited good cytocompatibility and strong antibacterial activities against S. aureus and E. coli . Additionally, the hydrogel could be used for sutureless wound closure and displayed better advantages compared to sutures and commercial adhesive pads. The above results demonstrated that our non-swelling hydrogel adhesive with robust mechanical properties holds great promise for applications in clinical surgery.